Development of technology of boiled sausage from non-traditional raw materials - Tayeva, Aigul; Kozhakhiyeva, Madina; Jetpisbayeva, Bagila; Tlevlessova, Dinara; Samadun, Abdyssemat; Valiyv, Aivaz (Eastern-European Journal of Enterprise Technologies, 2023)
This paper considers the possibility of improving the functional and technological properties of boiled camel sausage with the addition of hump fat and chicken fillet. The effect of pumpkin peel powder on lipid oxidation, functional and technological properties of sausages from combined meat was investigated. Camel meat as a meat product has many advantages, for example, low fat content, high nutritional value, and its taste is barely distinguishable from beef. At the same time, it has the following disadvantages: sweetish taste, coarse-fiber structure; camel sausage has a lower shelf life compared to beef sausage; it is harder due to the content of hydroxyproline. To improve the functional and technological properties, dried rowan powder and pumpkin peel powder of the "Winter Sweet" variety, a zoned variety, were added in different quantities for comparison. The control sample was made in accordance with GOST for boiled sausage, with the replacement of fat with hump fat, and the replacement of beef with camel meat. For experimental samples, a plan for a full-factor experiment was built, taking into account the material balance. Additives varied in 3 levels, from 3 to 6 %. 7 samples with control were in total with the control sample being the sausage prepared according to the same recipe but without additives. There were three parallel experiments in each sample. It was revealed that hydrated rowan powder has a negative effect on taste but, at lower doses, it gives a spicy taste to the sausage while the addition of hydrated powder from pumpkin peels improves taste and organoleptic characteristics. Thus, one can conclude that waste in the form of pumpkin peels is also a valuable and useful product for improving the functional, technological, and organoleptic characteristics of sausage. The result of this study shows that when hydrated rowan powder and pumpkin peel powder are added, the problem of taste, aftertaste, smell, and shelf life is solved in the selected ratio, while the sausage also becomes more tender overall